A nano foam material and its preparation method and application
Through the deep freezing-two-step replacement-freeze-drying process, the problem of difficult to prepare PET nanofoams with high porosity and uniform nanocell structures in the prior art is solved, and the stable construction and regulation of multi-scale three-dimensional pore structures are achieved, reducing process complexity and cost.
Patent Information
- Application Number
- CN202211619550.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The prior art is difficult to prepare PET nanofoams with high porosity and uniform nanocell structure, and the preparation process is complex and costly.
Using a combined process of deep freezing-two-step displacement-freeze-drying, nanofoam materials with multi-scale three-dimensional pore structures are formed through the micro-phase separation and solvent replacement process of trifluoroacetic acid solvent.
The stable construction and regulation of multi-scale three-dimensional pore structure of nanofoam materials is achieved, reducing process complexity and cost, and improving the porosity and mechanical properties of the materials.
Smart Images

Figure CN116003972B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam material preparation, and in particular to a nano foam material and a preparation method and application thereof. Background Art
[0002] Porous polymer materials are generally obtained through a foaming process and are usually called polymer foam materials or polymer foams. They have the characteristics of low density, light weight, porosity, and high specific surface area. They are widely used in the fields of heat insulation, shock absorption, sound insulation, catalytic carriers, adsorption filtration, biological scaffolds, and lightweight structural materials and devices. Among them, polyethylene terephthalate (PET) foam has non-toxic and odorless properties, excellent flame retardancy, low smoke, non-toxic properties, and high temperature resistance (the maximum operating temperature for a short time can reach 200°C, and it can be used for a long time at 120°C. In addition, PET foam material is a thermoplastic material that can be recycled and reused. It has huge market prospects and is of great significance to achieving the "dual carbon" goals and circular economy.
[0003] Compared with PET foaming polymers with micron pores, foaming polymers with bubble diameters less than 1μm (nano foam) have attracted much attention because nano foams have higher porosity and uniform bubble diameters, better thermal insulation properties, and theoretically can also have light transmittance. As a high-end filter membrane, catalysis, and reaction platform carrier, they are at the forefront of international research and development. At present, PET nano foams with both high porosity and fine and uniform bubble diameters are still in the laboratory research or pilot research and development stage, and no practical materials have been developed on the market. From the perspective of pore size, PET nano foam can also be called PET nano foam or PET aerogel.
[0004] At present, the production and development of PET foam in China mainly focuses on overcoming the production difficulties of micron-pore PET foam and giving it multifunctionality, and there are few reports on PET nanofoam or PET aerogel. Polymer nanofoam or aerogel is mainly prepared by foaming method, sol-gel process or phase inversion method.
[0005] The Chinese invention patent application (CN114591528A) discloses a foamable flame-retardant PET polyester and a preparation method thereof. The Chinese invention patent application (CN114605623A) discloses a flexible PET-based copolyester and a bead foam prepared therefrom. The Chinese invention patent application (CN113912904A) discloses a specifically blended filling modified PET foam material and a molding method thereof. The above invention patents mainly overcome the problem of low melt strength and difficulty in foaming caused by the linear structure of the PET molecular chain by: 1) introducing long-chain branched dibasic acid or long-chain branched diol as the second, third or fourth comonomer during the PET polymerization process; 2) introducing toughening agents, bubble nucleating agents, etc. during the PET polyester synthesis process, thereby improving the mechanical properties of the PET foam. At the same time, functional components such as antioxidants, flame retardants, antibacterial agents, and aldehyde-free functional powders are added during the PET polymerization process to give the PET foam a variety of functionalities. However, the realization of the porous structure of PET foam requires modification of the PET molecular chain on the one hand, and the control process is complicated. On the other hand, supercritical gas (CO2) is ultimately required as a foaming agent for material foaming, and the cost of equipment and critical fluid is high, and the control process is complicated. In general, the above technologies solve the technical solutions for how to realize micron-pore PET foam and its functionality, and do not provide the realization technology and solution of PET nano foam.
[0006] A Chinese invention patent application (CN111793333A) discloses a method for preparing a PET foam core material for wind turbine blades. The above invention does not use supercritical gas as a foaming agent, but mainly increases the porous properties of the PET material through microcapsules and aerogel particles. However, the microcapsule synthesis process is complicated, and it is difficult to obtain a high porosity and uniform nanopore structure for the entire PET foam. A Chinese invention patent application (CN102585271A) discloses a method for supercritical CO2 foaming polyester. The above invention uses low-temperature supercritical CO2 to induce PET crystallization and ultimately obtain a PET nanoporous foam material. However, in general, the cost of the equipment and low-temperature critical fluid is high, and the control process is complicated.
[0007] The German invention patent with publication number DE10233703A1 discloses a method for producing nanoporous polymer foam, the specific process is as follows: a) dissolving a polymer in a sublimable solvent to form a polymer solution, b) cooling the polymer solution to a temperature below the melting point and maintaining the boiling point in the solvent for a maximum of 2 seconds to form a frozen mixture, and c) removing the frozen solvent by freeze drying to form a nanoporous polymer foam. However, the principle of forming pores in this method is to utilize the sublimation of the solvent from solid to gas, that is, directly changing from a frozen solid to a gas without forming a liquid phase. The method essentially obtains block-shaped aerogel particles bonded by an adhesive, and the presence of the adhesive will reduce the porosity of the entire aerogel; and the selected solvent has a carcinogenic effect, which is extremely harmful to the environment and freeze-drying equipment, and it is difficult to achieve continuous production. In addition, since the pores only come from the volatilization of the gas, the pore size is very small and difficult to control. Therefore, it is not suitable for the preparation of multi-scale pore structure polyester nanofoam materials.
[0008] In summary, polyester nanofoam or polyester aerogel has excellent performance and great application potential, but its preparation technology is still in the exploratory stage and deserves vigorous research and development. In view of this, it is necessary to design a nanofoam material and its preparation method and application to solve the above problems. Summary of the invention
[0009] Based on the above technical problems, the purpose of the present invention is to provide a nano foam material and a preparation method and application thereof.
[0010] To achieve the above-mentioned purpose, the present invention provides a nano foam material, which is a nano foam polyester material having a multi-scale three-dimensional pore structure formed by three nano hole structures interlaced with each other: micropores with a pore size of <2nm, mesopores with a pore size of 2.0-50nm, and macropores with a pore size of >50nm;
[0011] The macroscopic density of the nano foam material is 0.19-0.40 g / cm 3 , porosity is 70-90%;
[0012] The nano foam polyester material is composed of a single component of polyester;
[0013] Alternatively, the nano-foam polyester material is formed by a composite of polyester and a second phase polymer, the polyester and the second phase polymer are immiscible and composite with each other to form a skeleton interpenetrating network system, and the multi-scale three-dimensional pore structure is regulated by the second phase polymer;
[0014] Alternatively, the nano-foam polyester material is composited with polyester and a third phase polymer, and the multi-scale three-dimensional pore structure is regulated by a third phase polymer that is incompatible with the polyester and has an active functional group.
[0015] As a further improvement of the present invention, the polyester is one of PET, PBT, and a blend of PET and PBT.
[0016] As a further improvement of the present invention, the second phase polymer is deacetylated (75-85%) chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1.
[0017] As a further improvement of the present invention, the third phase polymer is a nanofiber having active functional groups; the mass ratio of the nanofiber to the polyester is (0.001-0.06):1.
[0018] As a further improvement of the present invention, the preparation method of the nano foam material is:
[0019] S1, preparation of a polymer homogeneous solution: dissolving a polyester masterbatch of a predetermined concentration in trifluoroacetic acid to prepare a polymer homogeneous solution;
[0020] S2, freezing: placing the polymer homogeneous solution in a container and freezing it at -40 to -80°C for 1 to 5 hours to obtain a frozen polymer;
[0021] S3, solvent replacement: pre-freeze the first replacement agent at -20 to -60°C for 1 to 5 hours, immerse the entire container containing the frozen polymer in the pre-freezing first replacement agent, and perform the first replacement treatment at -30 to -80°C for 48 to 96 hours to obtain a first gel polymer system; then, perform the second replacement treatment on the first gel polymer system at room temperature for 18 to 48 hours using the second replacement agent to obtain a second gel polymer system;
[0022] S4, freeze drying: freeze the second gel polymer system at -40 to -80°C for 18 to 36 hours, and then freeze dry it to obtain the nano foam material.
[0023] As a further improvement of the present invention, in step S3, the first displacing agent is one of isopropanol, ethanol, and a mixture of ethanol and isopropanol; the second displacing agent is one of tert-butanol and a mixture of tert-butanol and water;
[0024] In step S1, the volume ratio of the container to the first displacing agent is maintained at 1:(5-15).
[0025] As a further improvement of the present invention, in step S1, the concentration of the polyester masterbatch is 0.01 to 0.50 g / mL.
[0026] As a further improvement of the present invention, in step S1, the polymer homogeneous solution also includes a second phase polymer in a predetermined proportion.
[0027] As a further improvement of the present invention, in step S3, after the first replacement agent treatment and before the second replacement treatment, a third phase polymer in a predetermined proportion is added to the first gel polymer system.
[0028] As a further improvement of the present invention, the second phase polymer is deacetylated (75-85%) chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1.
[0029] As a further improvement of the present invention, the third phase polymer is a nanofiber having active functional groups; the mass ratio of the nanofiber to the polyester is (0.001-0.06):1.
[0030] As a further improvement of the present invention, the active functional group is one or a mixture of hydroxyl, amino, carboxyl, and amide bond.
[0031] To achieve the above-mentioned purpose, the present invention further provides a composite nano-foam material, wherein the composite nano-foam material is a composite foam material having a multi-scale three-dimensional pore structure formed by three nano-pore structures interlaced with each other: micropores with a pore size of <2nm, mesopores with a pore size of 2.0-50nm, and macropores with a pore size of >50nm;
[0032] The macroscopic density of the nano foam material is 0.19-0.40 g / cm 3 , porosity is 70-90%;
[0033] The composite nano foam material is formed by compounding polyester, a second phase polymer and a third phase polymer; the composite nano foam material is formed by compounding polyester, a second phase polymer and a third phase polymer.
[0034] As a further improvement of the present invention, the multi-scale three-dimensional pore structure of the composite nano foam material is jointly regulated by the synergistic effect of the second phase polymer that is incompatible with the polyester and the third polymer with active functional groups.
[0035] As a further improvement of the present invention, the ratio of the polyester, the second phase polymer and the third phase polymer is 1:(0.05-0.4):(0.001-0.06).
[0036] As a further improvement of the present invention, the preparation method of the nano foam material is:
[0037] P1, preparation of polymer homogeneous solution: dissolving polyester masterbatch and second phase polymer of predetermined concentration in trifluoroacetic acid to prepare polymer homogeneous solution;
[0038] P2, freezing: placing the polymer homogeneous solution in a container and freezing it at -40 to -80°C for 1 to 5 hours to obtain a frozen polymer;
[0039] P3, solvent replacement: pre-freeze the first replacement agent at -20 to -60°C for 1 to 5 hours, immerse the entire container containing the frozen polymer in the pre-freezing first replacement agent, maintain the volume ratio of the container to the first replacement agent at 1: (5 to 15), perform the first replacement treatment at -30 to -80°C for 48 to 96 hours, and obtain a first gel polymer system; then, add a predetermined proportion of the third phase polymer to the first gel polymer system at room temperature, and perform the second replacement treatment with the second replacement agent for 18 to 48 hours to obtain a second gel polymer system;
[0040] P4, freeze drying: freeze the second gel polymer system at -40 to -80°C for 18 to 36 hours, and then freeze dry it to obtain the composite nano foam material.
[0041] As a further improvement of the present invention, in step P3, the first displacing agent is one of isopropanol, ethanol, or a mixed solvent of isopropanol and ethanol; the second displacing agent is one of tert-butanol and a mixture of tert-butanol and water;
[0042] In step P1, the volume ratio of the container to the first displacing agent is maintained at 1:(5-15).
[0043] As a further improvement of the present invention, in step P1, the concentration of the polyester masterbatch is 0.01-0.50 g / mL; the second phase polymer is chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1.
[0044] As a further improvement of the present invention, in step P3, the third phase polymer is a nanofiber having active functional groups; the mass ratio of the nanofiber to the polyester is (0.001-0.06):1; the active functional groups are one or a mixture of hydroxyl, amino, carboxyl, amine, amide, and sulfonic acid groups.
[0045] To achieve the above-mentioned purpose of the invention, the present invention also provides the above-mentioned nano foam material, or the application of the above-mentioned composite nano foam material in the fields of sound insulation, heat insulation, adsorption filtration, biological scaffolds, lightweight structural material devices, etc.
[0046] The beneficial effects of the present invention are:
[0047] 1. The nano foam material provided by the present invention has a multi-scale three-dimensional pore structure formed by the interlacing of three nanopore structures: micropores with a pore size of <2nm, mesopores with a pore size of 2.0-50nm, and macropores with a pore size of >50nm, thereby overcoming the technical defect that polyester foam materials in the prior art are difficult to reach nanopore size.
[0048] 2. The preparation method of the nano foam material provided by the present invention is based on the combined process of deep freezing-two-step replacement-freeze drying to construct and regulate the multi-scale three-dimensional pore structure of the nano foam. Through the deep freezing process, the polyester polymer and the low freezing point trifluoroacetic acid solvent are crystallized to achieve microphase separation, forming a network system in which the solvent nanocrystals and the glassy porous polyester nano skeleton interpenetrate each other; then, at low temperature, the solid trifluoroacetic acid solvent in the crystalline state is directly replaced by a high freezing point first replacement agent, and the original solvent nanocrystals (solid trifluoroacetic acid solvent) are removed without changing the three-dimensional pore structure of the porous polyester nano skeleton; then, the first replacement agent is replaced by a second replacement agent with a low freezing point and high volatility. In the second replacement process at room temperature, the solid polymer system becomes a gel polymer system, and the second replacement agent fills the three-dimensional nanopores of the gel polymer to support the pore structure and prevent it from collapsing. After the final gel polymer system is freeze-dried, the second replacement agent is directly gasified, thereby obtaining a stable polyester nano foam structure. The two-step replacement process works synergistically to ensure that the three-dimensional nanoporous structure is not affected by morphological changes during the replacement process, and the three-dimensional pore structure can be stably maintained regardless of solid or gel state. The solution system is converted into a colloidal system through the first replacement, and the solvent with an extremely low freezing point (<-80°C) in the colloidal system is converted into a solvent with a freezing point near room temperature through the second replacement. The first replacement stabilizes the pore structure of the polymer due to the formation of a colloid; and the freezing point of the replacement agent in the second step lays the foundation for the solid-gas transformation of the solvent in the colloid during the subsequent vacuum freeze-drying, which lays the foundation for the formation of a stable pore structure. The synergistic effect of the two steps enables the three-dimensional structure to be stably maintained without causing any harm to the freeze-drying equipment.
[0049] 3. The preparation method of the nano foam material provided by the present invention, based on the single polyester, introduces a thermodynamically incompatible second phase polymer, realizes phase separation during deep freezing, and the glassy polyester, the glassy second phase polymer, and the solid crystallization solvent form an interpenetrating network porous skeleton to further increase the porosity. Alternatively, in the second step replacement process, the third phase polymer polymer nanofiber with active functional groups is introduced to further adjust the size, distribution and order of the pore structure of the polyester nano foam, and enhance the mechanical properties of the foam.
[0050] 4. The preparation method of the nano foam material provided by the present invention does not involve any complicated chemical reaction, and the process equipment is simple and easy to implement. The polyester nano foam finally formed can be obtained again through the same process cycle preparation, and has the characteristics of being recyclable and reusable.
[0051] 5. The composite nano foam material provided by the present invention combines polyester, second phase polymer and third phase polymer, and jointly regulates the multi-scale three-dimensional pore structure of the composite nano foam material through the mutual synergistic effect of the second phase polymer that is thermodynamically incompatible with polyester and the third polymer with active functional groups. At the same time, through the mutual synergistic effect between the second phase polymer and the third phase polymer, on the basis of enhancing the strength of the three-dimensional pore structure, the functional modification effect of the active functional groups can be used to give the foam material certain functionality, thereby expanding its application range and functionality. The use of active functional groups with functional modification effects, such as sulfonic acid groups, is used to enhance the adsorption performance of the filter material, or groups such as carboxyl groups, amine groups, imine groups and amide groups are beneficial to the adhesion and proliferation of cells, and are used for the affinity of biological scaffolds.
[0052] 6. The nano foam material provided by the present invention has potential application prospects in the fields of thermal insulation, adsorption filtration, bio-scaffolds and lightweight structural material devices based on the controllable multi-scale three-dimensional nano pore structure, recycling performance and simple and controllable preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Schematic diagram of the pore formation mechanism of PET nano foam provided by the present invention.
[0054] Figure 2 This is an electron microscope image of the surface of the PET nano foam prepared in Example 5 of the present invention (scale is nm).
[0055] Figure 3 This is an electron microscope image of the cross section of the PET nanofoam prepared in Example 5 of the present invention (scale is nm). DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0057] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0058] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0059] The present invention provides a nano foam material, which is a nano foam polyester material having a multi-scale three-dimensional pore structure formed by three nano hole structures interlaced with each other, namely, micropores with a pore size of less than 2nm, mesopores with a pore size of 2.0 to 50nm, and macropores with a pore size of more than 50nm;
[0060] The macroscopic density of the nano foam material is 0.19-0.40 g / cm 3 , porosity is 70-90%;
[0061] The nano foam polyester material is composed of a single component of polyester;
[0062] Alternatively, the nano foam polyester material is formed by a composite of polyester and a second phase polymer, wherein the polyester and the second phase polymer are composited to form a skeleton interpenetrating network system, and the multi-scale three-dimensional pore structure is regulated by the second phase polymer;
[0063] Alternatively, the nano-foam polyester material is formed by compounding polyester and a third phase polymer, and the multi-scale three-dimensional pore structure is regulated by the third phase polymer.
[0064] Preferably, the polyester is one of PET, PBT, and a blend of PET and PBT.
[0065] Preferably, the second phase polymer is deacetylated (75-85%) chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1.
[0066] Preferably, the third phase polymer is a nanofiber having active functional groups; the mass ratio of the nanofiber to the polyester is (0.001-0.06):1.
[0067] Preferably, the preparation method of the nano foam material is:
[0068] S1, preparation of a polymer homogeneous solution: dissolving a polyester masterbatch of a predetermined concentration in trifluoroacetic acid to prepare a polymer homogeneous solution;
[0069] S2, freezing: placing the polymer homogeneous solution in a container and freezing it at -40 to -80°C for 1 to 5 hours to obtain a frozen polymer;
[0070] S3, solvent replacement: pre-freeze a first replacement agent with a high freezing point (antifreeze) at -20 to -60°C for 1 to 5 hours, immerse the entire container containing the frozen polymer in the first replacement agent after pre-freezing, and perform a first replacement treatment at -30 to -80°C for 48 to 96 hours, wherein the first replacement agent directly replaces the solid trifluoroacetic acid solvent in a crystalline state to obtain a first gel polymer system; then, at room temperature, perform a second replacement treatment on the first gel polymer system using a second replacement agent with a low freezing point and high volatility for 18 to 48 hours to obtain a second gel polymer system;
[0071] S4, freeze drying: freeze the second gel polymer system at -40 to -80°C for 18 to 36 hours, and then freeze dry it to obtain the nano foam material.
[0072] Preferably, in step S3, the first displacing agent is one of isopropanol, ethanol, and a mixed solvent of ethanol and isopropanol; the second displacing agent is one of tert-butanol and a mixture of tert-butanol and water;
[0073] In step S1, the volume ratio of the container to the first displacing agent is maintained at 1:(5-15).
[0074] Preferably, in step S1, the concentration of the polyester masterbatch is 0.01 to 0.50 g / mL.
[0075] Preferably, in step S1, the polymer homogeneous solution further comprises a second phase polymer in a predetermined proportion. The second phase polymer is immiscible with the polyester but both are soluble in trifluoroacetic acid solvent.
[0076] Preferably, in step S3, after the first displacement agent treatment and before the second displacement treatment, a third phase polymer in a predetermined proportion is added to the first gel polymer system.
[0077] Preferably, the second phase polymer is chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1; the third phase polymer is nanofibers with active functional groups; the mass ratio of nanofibers to polyester is (0.001-0.06):1.
[0078] The present invention also provides a composite nano foam material, which is a composite foam material with a multi-scale three-dimensional pore structure formed by three nano-pore structures interlaced with each other, namely, micropores with a pore size of <2nm, mesopores with a pore size of 2.0-50nm, and macropores with a pore size of >50nm;
[0079] The macroscopic density of the composite nano foam material is 0.19-0.40 g / cm 3 , porosity is 70-90%;
[0080] The composite nano foam material is formed by mutually compounding polyester, second phase polymer and third phase polymer; the ratio of the polyester, second phase polymer and third phase polymer is 1:(0.05-0.4):(0.001-0.06).
[0081] Preferably, see Figure 1 As shown, the preparation method of the nano foam material is:
[0082] P1, preparation of polymer homogeneous solution: dissolving polyester masterbatch and second phase polymer of predetermined concentration in trifluoroacetic acid to prepare polymer homogeneous solution;
[0083] P2, freezing: placing the polymer homogeneous solution in a container and freezing it at -40 to -80°C for 1 to 5 hours to obtain a frozen polymer;
[0084] P3, solvent replacement: pre-freeze the first replacement agent at -20 to -60°C for 1 to 5 hours, immerse the entire container containing the frozen polymer in the pre-freezing first replacement agent, maintain the volume ratio of the container to the first replacement agent at 1: (5 to 15), perform the first replacement treatment at -30 to -80°C for 48 to 96 hours, and obtain a first gel polymer system; then, add a predetermined proportion of the third phase polymer to the first gel polymer system at room temperature, and perform the second replacement treatment with the second replacement agent for 18 to 48 hours to obtain a second gel polymer system;
[0085] P4, freeze drying: freeze the second gel polymer system at -40 to -80°C for 18 to 36 hours, and then freeze dry it to obtain the composite nano foam material.
[0086] Preferably, in step P3, the first displacing agent is one of isopropanol, ethanol, and a mixed solvent of ethanol and isopropanol; the second displacing agent is one of tert-butanol and a mixture of tert-butanol and water;
[0087] In step P1, the volume ratio of the container to the first displacing agent is maintained at 1:(5-15).
[0088] Preferably, in step P1, the concentration of the polyester masterbatch is 0.01-0.50 g / mL; the second phase polymer is chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1.
[0089] Preferably, in step P3, the third phase polymer is a nanofiber having an active functional group; the mass ratio of the nanofiber to the polyester is (0.001-0.06):1; the active functional group is one or a mixture of hydroxyl, amino, carboxyl, amine, amide, and sulfonic acid.
[0090] Example 1
[0091] Embodiment 1 of the present invention provides a method for preparing a PET nano foam material, and the specific preparation process is as follows:
[0092] S1, preparation of polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.09 g / mL, and magnetic stirring was used for 24 hours to finally form a clear polymer homogeneous solution system that did not settle within one week.
[0093] S2, freezing of the solution (liquid-solid phase conversion): take an appropriate amount of the above polymer homogeneous solution and dispense it into polytetrafluoroethylene containers of different shapes and capacities; place multiple containers in a -70°C low-temperature refrigerator for 2 hours to allow the polymer homogeneous solution system to transform from liquid to solid.
[0094] S3, two-step solvent replacement: use isopropanol as the first replacement agent and pre-freeze at -30°C for 3 hours. Immerse the entire container containing the frozen polymer system in the low-temperature isopropanol solvent, maintain the volume ratio of the frozen polymer container to isopropanol at 1:9, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -50°C for 64 hours. During this period, stir the system every 12-14 hours, remove 1 / 3 of the volume of the solvent in the system, and replenish the isopropanol solvent to the original volume. After the isopropanol is completely replaced, the above-mentioned gel system is subjected to the second replacement treatment at room temperature using tert-butyl alcohol solvent (second replacement agent) for 30 hours.
[0095] S4, freeze drying: the replaced gel system is sealed and placed in a -70°C low-temperature refrigerator for 24 hours, then taken out and placed in a freeze dryer with a cold trap temperature of -80°C for 48 hours to finally obtain a white nano foam material.
[0096] After testing, the macroscopic density of the nano foam material is 0.249 g / cm 3 , the porosity is 80.58±0.09%.
[0097] Example 2
[0098] The difference from Example 1 is that the polymer homogeneous solution system in step S1 also includes a second phase polymer. The specific process is: PET polyester masterbatch is dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.09 g / mL, and chitosan with a mass percentage of 20% of PET is added to the above solution. Magnetic stirring is used for 24 hours to finally form a clear mixed homogeneous solution system that does not settle within one week.
[0099] The rest is the same as that of Example 1 and will not be described again.
[0100] The nano foam material prepared in Example 2 has a macroscopic density of 0.261 g / cm 3 , the porosity is 82.2%±0.04%.
[0101] Example 3
[0102] The difference from Example 1 is that: in step S3, solvent replacement: isopropanol is used as the first replacement agent, and pre-frozen at -30°C for 3 hours. The container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent as a whole, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:9, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -50°C for 64 hours. During this period, the system is stirred every 12-14 hours, and 1 / 3 of the volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. Then at room temperature, the third phase polymer nanofiber suspension (nanofibers are 0.33% of the mass of PET) is added to the first gel polymer system, and after the isopropanol is completely replaced, the above-mentioned gel system is subjected to the second replacement treatment for 30 hours at room temperature using tert-butyl alcohol solvent (second replacement agent).
[0103] The preparation method of the nanofiber suspension is as follows: the nanofiber suspension is placed in an alcohol-water system, and a uniformly dispersed milky white nanofiber dispersion with a concentration of 10 mg / mL is obtained by strong shearing of the agitator. The nanofiber has active functional groups such as hydroxyl, amino or amide groups.
[0104] The rest is the same as that of Example 1 and will not be described again.
[0105] The nano foam material prepared in Example 3 has a macroscopic density of 0.252 g / cm 3 , the porosity is 84.1%±0.03%.
[0106] Example 4
[0107] Embodiment 4 of the present invention provides a method for preparing a PET nano foam material, and the specific preparation process is as follows:
[0108] S1, preparation of nanofiber suspension: placing the nanofiber suspension in an alcohol-water system, and obtaining a uniformly dispersed milky white nanofiber dispersion with a concentration of 10 mg / mL through strong shearing action of a stirrer.
[0109] S2, preparation of polymer solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.18 g / mL, and magnetic stirring was used for 24 hours to finally form a clear solution system.
[0110] S3, freezing of solution (liquid-solid phase conversion): Take appropriate amount of the above solution and dispense it into polytetrafluoroethylene containers of different shapes and capacities. Place multiple small containers in a -80°C low-temperature refrigerator for 2-3 hours to allow the polymer system to transform from liquid to solid.
[0111] S4, two solvent replacements: isopropanol is used as the first replacement agent, and pre-freeze at -20℃ for 3-5 hours. The small container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:10, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -50℃, and the replacement process lasts for 24 hours. During this period, the system is stirred every 4-6 hours, and 1 / 3 of the volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. Then, at room temperature, the third phase polymer nanofiber suspension (nanofibers are 0.2% of the mass of PET) is added to the first gel polymer system. After the isopropanol is completely replaced, the above gel system is replaced again at room temperature with a second replacement agent, a mixed solvent of tert-butanol and water (tert-butanol / water, v / v=9:1) for 24 hours.
[0112] S5, freeze drying: the sol system after the replacement is sealed and placed in a -80℃ low temperature refrigerator for 36 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -60℃ for 48 hours. Finally, a white nano foam material is obtained. Its macroscopic density is 0.343g / cm 3 , the porosity is 74.44±0.16%.
[0113] Example 5
[0114] Embodiment 5 of the present invention provides a method for preparing a PET nano foam material, and the specific preparation process is as follows:
[0115] S1, preparation of mixed polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.03 g / mL, and chitosan (26.7% by weight of PET) was added to the above solution, and magnetic stirring was used for 24 hours to finally form a clear mixed homogeneous solution system that did not settle within one week.
[0116] S2, directional freezing of the solution (rapid liquid-solid phase conversion): Take an appropriate amount of the above solution and divide it into polytetrafluoroethylene containers of different shapes and capacities. Place multiple small containers on the upper end surface of the copper mold in the liquid nitrogen insulation tank, and quickly add liquid nitrogen under the copper mold until it covers the bottom of the container, so that the solution is rapidly directionally frozen and quickly changes from liquid to solid. Cover the insulation tank and keep it warm for 1 minute. Repeat the above liquid nitrogen addition process 2-3 times until the solution is completely frozen. Store the frozen polymer system together with the container in a -80°C low-temperature refrigerator to allow the solvent and the two-phase polymer to fully crystallize.
[0117] S3, two solvent replacements: use isopropanol as the first replacement agent and pre-freeze at -30°C for 2-4 hours. Immerse the above small container containing the frozen polymer system in the low-temperature isopropanol solvent, maintain the volume ratio of the frozen polymer container to isopropanol at 1:9, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -60°C, and the replacement process lasts for 64 hours. During this period, stir the system every 12-14 hours, remove 1 / 3 of the volume of the solvent in the system, and replenish the isopropanol solvent to the original volume. After the isopropanol is completely replaced, the above gel system is replaced in two steps using tert-butanol solvent at room temperature for 30 hours.
[0118] S4, freeze drying: the sol system after the replacement is sealed and placed in a -70°C low-temperature refrigerator for 24-48 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -60°C for 48 hours to finally obtain a white nano foam material.
[0119] Its macroscopic density is 0.193 g / cm 3 The porosity is 84.79±0.14%. The internal pore structure is as shown in the attached manual. Figure 2 and 3 As shown, Figure 2 This is the surface SEM picture of PET nanofoam. Figure 3 This is the cross-sectional SEM photograph.
[0120] from Figure 2-3 It can be seen that the nanopore structure is composed of three nanopore structures: micropores with a pore size of <2nm, mesopores with a pore size of 2.0-50nm, and macropores with a pore size of >50nm.
[0121] Example 6
[0122] Please refer to Figure 1 As shown, Example 6 of the present invention provides a PET composite nano foam material, and the specific preparation process is as follows:
[0123] P1, preparation of nanofiber suspension: the nanofiber suspension is placed in an alcohol-water system, and a uniformly dispersed milky white nanofiber dispersion with a concentration of 10 mg / mL is obtained through strong shearing action of a stirrer.
[0124] P2, preparation of mixed polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.09 g / mL, and chitosan (20% by mass of PET) was added to the above solution. Magnetic stirring was used for 24 hours to finally form a clear mixed homogeneous solution system that did not settle within one week.
[0125] P3, freezing of solution (fast liquid-solid phase conversion): Take appropriate amount of the above solution and divide it into polytetrafluoroethylene containers of different shapes and capacities. Place multiple small containers in a liquid nitrogen insulation tank, quickly add liquid nitrogen until it covers the bottom of the container, so that the solution is quickly frozen and quickly changes from liquid to solid. Cover the insulation tank and keep it warm for 2 minutes. Repeat the above liquid nitrogen addition process 2-3 times until the solution is completely frozen. Store the frozen polymer system together with the container in a -80℃ low-temperature refrigerator to allow the solvent and the two-phase polymer to fully crystallize.
[0126] P4, two solvent replacements: isopropanol is used as the first replacement agent, and pre-freeze at -40℃ for 2-4 hours. The small container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:10; the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -50℃, and the replacement process lasts for 72 hours. During this period, the system is stirred every 4-6 hours, and 1 / 4 volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. The third phase polymer nanofiber suspension (nanofibers are 0.33% of the mass of PET) is added to the first gel polymer system. After the isopropanol is completely replaced, the above gel system is replaced in two steps at room temperature using a second replacement agent of tert-butyl alcohol and a mixed solvent of water (tert-butyl alcohol / water, v / v=3:1) for 48 hours.
[0127] P5, freeze drying: the sol system after the replacement is sealed and placed in a -70°C low-temperature refrigerator for 24-48 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -80°C for 48 hours. Finally, a white nano foam material is obtained.
[0128] The nanofibers have hydroxyl and amino active functional groups, which can interact with the active groups on chitosan, and the two are stably compounded to synergistically enhance the mechanical strength.
[0129] The nano foam material prepared in Example 6 has a macroscopic density of 0.40 g / cm3 , the porosity is 73.31±006%.
[0130] Example 7
[0131] Embodiment 7 of the present invention provides a PET composite nano foam material, and the specific preparation process is as follows:
[0132] P1, preparation of nanofiber suspension: the nanofiber suspension is placed in an alcohol-water system, and a uniformly dispersed milky white nanofiber dispersion with a concentration of 10 mg / mL is obtained through strong shearing action of a stirrer.
[0133] P2, preparation of mixed polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.04 g / mL, and chitosan (20% by mass of PET) was added to the above solution. Magnetic stirring was used for 24 hours to finally form a clear mixed homogeneous solution system that did not settle within one week.
[0134] P3, freezing of solution (liquid-solid phase conversion): Take appropriate amount of the above solution and dispense it into polytetrafluoroethylene containers of different shapes and capacities. Place several small containers in a -60℃ low-temperature refrigerator for 3-4 hours to allow the polymer system to transform from liquid to solid.
[0135] P4, two solvent replacements: isopropanol is used as the first replacement agent, and pre-freeze at -30°C for 3-5 hours. The small container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:8, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -60°C, and the replacement process lasts for 24 hours. During this period, the system is stirred every 5-6 hours, and 1 / 4 volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. The third phase polymer nanofiber suspension (nanofibers are 0.75% of the mass of PET) is added to the first gel polymer system. After the isopropanol is completely replaced, the above gel system is replaced in two steps at room temperature using a second replacement agent, a mixed solvent of tert-butanol and water (tert-butanol / water, v / v=1:1) for 24 hours.
[0136] P5, freeze drying: the sol system after the replacement is sealed and placed in a -50°C low-temperature refrigerator for 36 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -70°C for 48 hours. Finally, a white nano foam material is obtained.
[0137] Its macroscopic density is 0.241 g / cm 3 , the porosity is 79.14±0.03%.
[0138] Example 8
[0139] Embodiment 8 of the present invention provides a PET composite nano foam material, and the specific preparation process is as follows:
[0140] P1, preparation of nanofiber suspension: the nanofiber suspension is placed in an alcohol-water system, and a uniformly dispersed milky white nanofiber dispersion with a concentration of 10 mg / mL is obtained through strong shearing action of a stirrer.
[0141] P2, preparation of mixed polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.06 g / mL, and chitosan (20% by mass of PET) was added to the above solution. Magnetic stirring was used for 24 hours to finally form a clear mixed homogeneous solution system that did not settle within one week.
[0142] P3, freezing of solution (liquid-solid phase conversion): Take appropriate amount of the above solution and dispense it into polytetrafluoroethylene containers of different shapes and capacities. Place several small containers in a -60℃ low-temperature refrigerator for 3-4 hours to allow the polymer system to transform from liquid to solid.
[0143] P4, two solvent replacements: isopropanol is used as the first replacement agent, and pre-freeze at -30°C for 3-5 hours. The small container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:8, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. The first replacement treatment is carried out at -40°C. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the replacement process lasts for 24 hours. During this period, the system is stirred every 5-6 hours, and 1 / 4 volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. The third phase polymer nanofiber suspension (nanofibers are 0.5% of the mass of PET) is added to the first gel polymer system. After the isopropanol is completely replaced, the above gel system is replaced for a second time at room temperature using a mixed solvent of tert-butanol and water (tert-butanol / water, v / v=1:1) as the second replacement agent for 24 hours.
[0144] P5, freeze drying: the sol system after the replacement is sealed and placed in a -50°C low-temperature refrigerator for 36 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -80°C for 48 hours. Finally, a white nano foam material is obtained.
[0145] Its macroscopic density is 0.217 g / cm 3 , the porosity is 83.9±0.7%.
[0146] Example 9
[0147] Embodiment 9 of the present invention provides a PET nano foam material, and the specific preparation process is as follows:
[0148] S1, preparation of mixed polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.075 g / mL, and chitosan (16% by mass of PET) was added to the above solution, and magnetic stirring was used for 24 hours to finally form a clear mixed homogeneous solution system that did not settle within one week.
[0149] S2, freezing of solution (liquid-solid phase conversion): Take appropriate amount of the above solution and dispense it into polytetrafluoroethylene containers of different shapes and capacities. Place multiple small containers in a -50°C low-temperature refrigerator for 4-5 hours to allow the polymer system to transform from liquid to solid.
[0150] S3, two solvent replacements: isopropanol is used as the first replacement agent, and pre-freeze at -50°C for 3-5 hours. The small container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:10, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -70°C, and the replacement process lasts for 24 hours. During this period, the system is stirred every 4-6 hours, and 1 / 3 of the volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. After the isopropanol is completely replaced, the above-mentioned gel system is replaced for a second time at room temperature using a mixed solvent of tert-butanol and water (tert-butanol / water, v / v=19:1) as the second replacement agent for 24 hours.
[0151] S4, freeze drying: the sol system after the replacement is sealed and placed in a -40°C low-temperature refrigerator for 24 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -60°C to 80°C for 48 hours. Finally, a white nano foam material is obtained.
[0152] Its macroscopic density is 0.235 g / cm 3 , the porosity is 81.26±0.07%.
[0153] Example 10
[0154] Embodiment 10 of the present invention provides a PET composite nano foam material, and the specific preparation process is as follows:
[0155] P1, preparation of nanofiber suspension: the nanofiber suspension is placed in an alcohol-water system, and a uniformly dispersed milky white nanofiber dispersion with a concentration of 10 mg / mL is obtained through strong shearing action of a stirrer.
[0156] P2, preparation of mixed polymer homogeneous solution system: PET polyester masterbatch was dissolved in pure trifluoroacetic acid (purity>95%) at a concentration of 0.09 g / mL, and chitosan (13.3% of the mass of PET) was added to the above solution, and magnetic stirring was used for 24 hours to finally form a clear mixed homogeneous solution system that did not settle within a week. Then, 3% of the volume of the mixed homogeneous solution system of nanofiber suspension was added to the above solution, and stirred for dissolution and dispersion for 5 minutes.
[0157] P3, freezing of solution (liquid-solid phase conversion): Take appropriate amount of the above solution and dispense it into polytetrafluoroethylene containers of different shapes and capacities. Place several small containers in a -80℃ low-temperature refrigerator for 4-5 hours to allow the polymer system to transform from liquid to solid.
[0158] P4, two solvent replacements: isopropanol is used as the first replacement agent, and pre-freeze at -20°C for 3-5 hours. The small container containing the frozen polymer system is immersed in the low-temperature isopropanol solvent, and the volume ratio of the frozen polymer container to isopropanol is maintained at 1:9, so that the crystallized solid trifluoroacetic acid is slowly dissolved and replaced by isopropanol. During the replacement process, the frozen polymer changes from a solid state to a semi-gel state, and the first replacement treatment is carried out at -60°C, and the replacement process lasts for 36 hours. During this period, the system is stirred every 6-8 hours, and 1 / 4 volume of the solvent in the system is removed, and the isopropanol solvent is supplemented to the original volume. The third phase polymer nanofiber suspension (nanofibers are 0.2% of the mass of PET) is added to the first gel polymer system. After the isopropanol is completely replaced, the above gel system is replaced for a second time at room temperature using a mixed solvent of tert-butanol and water (tert-butanol / water, v / v=9:1) as the second replacement agent for 20 hours.
[0159] P5, freeze drying: the sol system after the replacement is sealed and placed in a -80°C low-temperature refrigerator for 48 hours. Then it is taken out and placed in a freeze dryer with a cold trap temperature of -60°C for 48 hours. Finally, a white nano foam material is obtained.
[0160] Its macroscopic density is 0.389 g / cm 3 , the porosity is 72.21±0.03%.
[0161] Embodiment 11
[0162] The difference from Example 1 is that polyester PBT (butylene terephthalate) is used as the polyester masterbatch. Other details are the same as in Example 1 and will not be described again. A PBT foam material is prepared.
[0163] Example 12
[0164] The difference from Example 6 is that polyester PBT (butylene terephthalate) is used as the polyester masterbatch. Other details are the same as Example 6 and will not be repeated here. A PBT foam composite material is prepared.
[0165] Example 13
[0166] The difference from Example 6 is that nanofibers with functional modification active functional groups (sulfonic acid groups, used to enhance the adsorption performance of the filter material) are used. The other steps are the same as Example 6 and will not be repeated here to prepare a PET foam composite material.
[0167] Table 1 shows the performance parameters of Examples 1-10
[0168]
[0169] Combining Table 1 with the parameter settings of Examples 1 to 10, it can be seen that the temperature of deep freezing, the temperature and time setting of the first substitution process, the type of substitution agent and the substitution time of the second substitution process will have a certain regulatory effect on the three-dimensional pore structure of the foam material. The lower the temperature of deep freezing, the faster the freezing speed leads to a smaller pore size, but a higher porosity; the longer the freezing time, the larger the pore size and the higher the porosity; the lower the temperature of the first substitution process, the higher the porosity; the higher the content of tert-butyl alcohol in the second substitution process, the more complete the structure of the foam.
[0170] The change in the ratio between polyester and the second phase / three-phase polymer will also have a regulatory effect on the three-dimensional pore structure. The higher the concentration of pure PET, the greater the density of the final foam and the smaller the porosity; adding the second phase polymer, as the content of the second phase polymer increases (the density of the second phase polymer is greater than the first phase), the density of the foam increases, and the porosity increases at the same time; adding the third phase nanofiber polymer, the density decreases relative to the two-phase system, but at the same time the porosity increases slightly, and the foam has better formability.
[0171] It should be noted that those skilled in the art should understand that the polyester in the embodiment of the present invention can also be one of the PET / PBT blend polymers. The active functional groups of the third phase polymer in the embodiment of the present invention can also be adaptively adjusted according to the actual application requirements, for example, the use of active groups such as carboxyl, amine, imine and amide groups in the field of biological scaffolds is beneficial to the adhesion and proliferation of cells and is used to enhance the affinity of biological scaffolds.
[0172] In summary, the present invention provides a nano foam material and its preparation method and application. The nano foam material is a nano foam polyester material with a multi-scale three-dimensional pore structure formed by three nano hole structures, namely, micropores with a pore size of <2nm, mesopores with a pore size of 2.0 to 50nm, and macropores with a pore size of >50nm. The preparation method of the nano foam material provided by the present invention does not involve any complex chemical reactions, and the process equipment is simple and easy to implement. And the polyester nano foam finally formed can be obtained again through the same process cycle preparation, and has the characteristics of being recyclable and reusable. Based on the adjustable multi-scale three-dimensional nano pore structure, the recyclable use performance and the simple and controllable preparation process, the nano foam material has potential application prospects in the fields of thermal insulation, adsorption filtration, bio-scaffolds and lightweight structural material devices.
[0173] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A nano foam material, characterized in that: The nano foam material is a nano foam polyester material with a multi-scale three-dimensional pore structure formed by the interlacing of three nano hole structures: micropores with a pore size of <2nm, mesopores with a pore size of 2.0-50nm, and macropores with a pore size of >50nm; The macroscopic density of the nano foam material is 0.19-0.40 g / cm 3 , porosity is 70-90%; The nano foam polyester material is composed of a single component of polyester; Alternatively, the nano-foam polyester material is formed by a composite of polyester and a second phase polymer, the polyester and the second phase polymer are thermodynamically immiscible and composite with each other to form a skeleton interpenetrating network system, and the multi-scale three-dimensional pore structure is regulated by the second phase polymer; Alternatively, the nano-foam polyester material is formed by a composite of polyester and a third phase polymer, and the multi-scale three-dimensional pore structure is regulated by a third phase polymer that is incompatible with the polyester and has an active functional group; The second phase polymer is chitosan, and the mass ratio of chitosan to polyester is (0.05-0.4):1; The third phase polymer is a nanofiber with active functional groups; the mass ratio of the nanofiber to the polyester is (0.001-0.06):1; The polyester is one of PET, PBT, and a blend of PET and PBT; The preparation method of the nano foam material is: S1, preparation of a polymer homogeneous solution: dissolving a polyester masterbatch of a predetermined concentration in trifluoroacetic acid to prepare a polymer homogeneous solution; S2, freezing: placing the polymer homogeneous solution in a container, and freezing it at -40 to -80°C for 1 to 5 hours to obtain a frozen polymer; S3, solvent replacement: immersing the entire container containing the frozen polymer in a first replacement agent that has been pre-frozen at low temperature, performing a first replacement treatment at -30 to -80°C for 48 to 96 hours to obtain a first gel polymer system; then, at room temperature, performing a second replacement treatment on the first gel polymer system using a second replacement agent for 18 to 48 hours to obtain a second gel polymer system; S4, freeze drying: freezing the second gel polymer system at -40 to -80°C for 18 to 36 hours, and then freeze drying the system to obtain the nano foam material; In step S3, the first displacing agent is one of isopropanol, ethanol, and a mixed solvent of ethanol and isopropanol; the second displacing agent is one of tert-butanol and a mixture of tert-butanol and water; In step S1, the volume ratio of the container to the first displacing agent is maintained at 1:(5-15).
2. A nano foam material according to claim 1, characterized in that: In step S1, the concentration of the polyester masterbatch is 0.01-0.50 g / mL.
3. The nano foam material according to claim 1, characterized in that: In step S1, the polymer homogeneous solution also includes a second phase polymer in a predetermined proportion.
4. The nano foam material according to claim 1, characterized in that: In step S3, after the first replacement treatment and before the second replacement treatment, a third phase polymer in a predetermined proportion is added to the first gel polymer system.
5. A composite nano foam material, characterized in that: The composite nano foam material is a composite foam material with a multi-scale three-dimensional pore structure formed by the interlacing of three nanopore structures: micropores with a pore size of <2 nm, mesopores with a pore size of 2.0-50 nm, and macropores with a pore size of >50 nm. The macroscopic density of the composite nano foam material is 0.19-0.40 g / cm 3 , porosity is 70-90%; The composite nano foam material is formed by asynchronously compounding polyester, a second phase polymer that is thermodynamically incompatible with the polyester, and a third phase polymer with active functional groups. The mass ratio of the polyester, the second phase polymer and the third phase polymer is 1: (0.05-0.4): (0.001-0.06); The preparation method of the composite nano foam material is: P1, preparation of polymer homogeneous solution: dissolving polyester masterbatch and second phase polymer of predetermined concentration in trifluoroacetic acid to prepare polymer homogeneous solution; P2, freezing: placing the polymer homogeneous solution in a container and freezing it at -40 to -80°C for 1 to 5 hours to obtain a frozen polymer; P3, solvent replacement: immerse the entire container containing the frozen polymer in the first replacement agent that has been pre-frozen at low temperature, maintain the volume ratio of the container to the first replacement agent at 1: (5-15), and perform the first replacement treatment at -30--80°C for 48-96 hours to obtain a first gel polymer system; then, add a predetermined proportion of the third phase polymer to the first gel polymer system at room temperature, and use the second replacement agent to perform the second replacement treatment for 18-48 hours to obtain a second gel polymer system; P4, freeze drying: freezing the second gel polymer system at -40 to -80°C for 18 to 36 hours, and then freeze drying to obtain the composite nano foam material; In step P3, the first displacing agent is one of isopropanol, ethanol, and a mixed solvent of ethanol and isopropanol; the second displacing agent is one of tert-butanol and a mixture of tert-butanol and water; In step P1, the volume ratio of the container to the first displacing agent is maintained at 1:(5-15).
6. The composite nano foam material according to claim 5, characterized in that: In step P1, the concentration of the polyester masterbatch is 0.01-0.50 g / mL; the second phase polymer is chitosan; In step P3, the third phase polymer is a nanofiber having active functional groups; the active functional groups are one or a mixture of hydroxyl, amino, carboxyl, amine, amide, and sulfonic acid groups.
7. Use of a nano foam material as claimed in any one of claims 1 to 4, or a composite nano foam material as claimed in any one of claims 5 to 6 in the fields of sound insulation, heat insulation, adsorption filtration, bio-scaffold, and lightweight structural material devices.
Citation Information
Patent Citations
Method for preparing nano-pore structured polyethylene terephthalate (PET) foams by foaming through supercritical CO2
CN102585271A
Preparation method of PET foam core material for wind turbine blade
CN111793333A
Blending filling modified PET foaming material and forming method thereof
CN113912904A
Foamable flame-retardant PET polyester and preparation method thereof
CN114591528A
Flexible PET (Polyethylene Terephthalate)-based copolyester and bead foam prepared from flexible PET-based copolyester
CN114605623A